Upaya Meningkatkan Minat Membaca Anak Menggunakan Metode Reading Aloud - Yeni Susilawati; Muhajirin Ramzi; Musafir Musafir (Jurnal Pembelajaran dan Pendidikan Dasar, 2024)
This research aims to improve children's interest in reading through the Reading Aloud method at TKN Dewi Sartika Gondang for the 2022/2023 Academic Year.  This research was conducted at TKN Dewi Sartika Gondang with a total of 20 children consisting of 10 boys and 10 girls.  This research uses classroom action research techniques (PTK The research subjects are 20 children in group B. The objects of this research use data collection techniques, interviews, observation and documentation in the form of pictures and videos. The data analysis techniques used are qualitative and quantitative techniques. The research can be said to be successful if it reaches a score or criterion of 80.The results of the research conducted showed that the Reading Aloud method in pre-action and pra sikha only reached 30% in cycle I increased to 55% and in cycle II increased to 85%.  So it can be concluded that using the Reading Aloud method can increase children's reading interest. The choice of media in reading books and book reading techniques also have an important effect on increasing children's interest in reading because children will be more enthusiastic about listening if the media or books and the way in which they are presented use interesting methods and the media used is interesting and appropriate for their age.  The research was stopped in cycle II because it had reached the success criteria.